1.- 3(x - 2) = 15
Solve for x 3(x - 2)/3 = 15/3
Simplifying x - 2 = 5
(x - 2) = 15/3
(x - 2) = 5
x - 2 = 5
x = 5 + 2
x = 7
Check. Substitute the value of x in the original equation and solve it
3(7 - 2) = 15
3(5) = 15
15 = 15 As the two value are the same, the solution of x is
correct.
2.- 4y + 9 - 7y = -6
Solve for y
Simplify like terms
4y - 7y + 9 = -6
- 3y + 9 = -6
-3y = -6 - 9
-3y = -15
-3y/-3 = -15/-3
y = 5
Check
4(5) + 9 - 7(5) = -6
20 + 9 - 35 = -6
29 - 35 = -6
-6 = -6 The solution is correct because both numbers are the same.